Management of sucking insect pests of tomato (Solanum lycopersicum) with insecticides and their impact on beneficial arthropods - MONDAL, AMBIKA RANI; MIAH, MD RAMIZ UDDIN; MIAH, MD YUNUS; AFROZ, MANSURA; MAZED, MD KHAIRUL; SUH, SANG JAE; AMIN, MD RUHUL (The Indian Journal of Agricultural Sciences, 2023)
The present study was carried out at the research field of the Department of Entomology, Bangabandhu Sheikh Mujibur Rahman Agricultural University, Gazipur, Bangladesh, during the tomato (Solanum lycopersicum L.) growing seasons of 2021 and 2022 to evaluate the pest management benefit of 4 insecticides, viz. Karate 2.5 ec (λ-cyhalothrin), Ripcord 10 ec (cypermethrin), Marshal 20 ec (carbosulfan), and Shobicron 425 ec (profenofos Q + cypermethrin) against sucking insect pests (aphids, jassids, whiteflies and thrips) of tomato. The abundance of the sucking pests was significantly lower in the insecticide treated plots compared with the untreated control. During both the years, carbosulfan was the most effective insecticide against aphids (3.1 and 0.8 aphids/3 leaves, respectively), jassids (0.1 and 0.7 jassid/3 leaves, respectively), and thrips (1.9 and 1.1 thrips/3 leaves, respectively), whereas the profenofos Q+ cypermethrin decreased the abundance of whiteflies (1.4 and 2.0 whiteflies/3 leaves, respectively). However, these insecticides had negative effects on the pollinator insect and natural enemies of sucking pests in tomato fields. The insecticide-treated plots showed a significantly lower number of predators and pollinator than the untreated control plots. In the 1st and 2nd years, plots treated with cypermethrin (1.1 predators/plant) and λ-cyhalothrin (1.2 predators/ plant), respectively, showed the highest abundance of predators. Among the insecticide-treated plots, profenofos Q + cypermethrin treated plots showed the highest abundance of pollinator in both years (1st year: 0.7/ plot and 2nd year: 0.9/ plot). Carbosulfan treated plot showed the highest mean yield (58.7 tonnes/ha) with the highest marginal benefit-cost ratio (5.1).